2005
DOI: 10.1080/10668920490891629
|View full text |Cite
|
Sign up to set email alerts
|

Part-time Community-College Faculty and The Desire for Full-time Tenure-Track Positions: Results Of a Single Institution Case Study

Abstract: According to data derived from a community-college survey in the state of Washington, the majority of part-time faculty prefer full-time work. Using a logit regression analysis, the study reported in this paper suggests that typical parttimers enter their part-time teaching situations with the intent of becoming fulltime, but gradually become discouraged. Those faculty who prefer their part-time status frequently maintain employment relations with one college for long periods of time. Faculty who persist in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…Part-time employment is almost always substantially less well paid, and much less likely to provide benefits. Although part-time faculty overall report positive job satisfaction (Anthony & Hayden, 2011;Jacoby, 2005;Kramer et al, 2014), discontent is evident in the number of union campaigns that have been waged related to adjunct and lecturer issues. At the same time, a number of research findings indicate that part-time working conditions affect student relationships and outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Part-time employment is almost always substantially less well paid, and much less likely to provide benefits. Although part-time faculty overall report positive job satisfaction (Anthony & Hayden, 2011;Jacoby, 2005;Kramer et al, 2014), discontent is evident in the number of union campaigns that have been waged related to adjunct and lecturer issues. At the same time, a number of research findings indicate that part-time working conditions affect student relationships and outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These involve the separate impacts it has on faculty and upon students. Researchers have found that about half of all part-time academics would prefer full-time employment that provides greater security and benefits (Jacoby, 2005). However, given the current structure of jobs a minority of faculty make this transition (Finkelstein et al, 2016).…”
Section: Policy Implicationsmentioning
confidence: 99%
“…The teaching load can also vary depending on the instructor's rank in the university, as pointed out by García-Gallego et al (2012). Thus, adjunct lecturers, who work as part-time instructors, may feel unmotivated to teach because they earn lower salaries than full-time professors, and this may negatively affect students' academic performance (Jacoby, 2005). Assistant professors who seek promotion may make greater effort for research than for teaching, compared to associate or full-time professors who hold a tenure-track position at the university.…”
Section: ▪ 30 Universidad De Medellínmentioning
confidence: 99%
“…This could be due to: (1) The different training levels of full-time and parttime professors. According to Benjamin (2003), the percentage of doctorate professors among full-time professors is higher than the percentage of doctorate professors among part-time professors; (2) The shorter amount of time professors are available to interact with students, and implement changes in their teaching methods, according to Benjamin (2002) and Umbach (2007); (3) The lack of motivation of this group of professors, who earn much lower salaries than fulltime professors, according to Jacoby (2005); (4) The inefficiency of the subject coordinators to assign teaching hours to subjects related to the development of…”
Section: Introductionmentioning
confidence: 99%
“…In a single-institution study, Jacoby (2006b) found that 55.4 percent of part-time faculty at that two-year college desired full-time work. These faculty members were more likely to teach the equivalent of a full-time load at their institution.…”
Section: A Profile Of Part-time Faculty At Community Collegesmentioning
confidence: 99%